ANALISIS SEMIOTIKA IKLAN TOKOPEDIA DI YOUTUBE: (Analisis Semiotika Roland Barthes Makna Pesan Pada Iklan Tokopedia Versi Berikan Yang Paling Berarti Untuk Yang Berarti) - Stefani Ardya garini (Solidaritas, 2022)
This research is an exploration of the meaning of the moral message contained in the selected scene of the Tokopedia advertisement version of Give The Most Meaningful For the Meaningful. The title of this research is semiotic analysis of Tokopedia advertisements on Yotube (Roland Barthes Semiotics Analysis of Message Meaning in Tokopedia advertisement version Give the Most Meaningful to Meaningful). A good composition must be able to support the delivery of the message contained in the advertisement. Researchers are interested in representing the meaning of the messages contained in the selected scene of the Tokopedia advertisement, Give the Most Meaningful For Meaningful Version. This research is descriptive qualitative. So that the data provided is not in the form of numbers or numbers. As a descriptive research, this research only describes the situation or discourse, does not look for relationships, and does not test hypotheses or make predictions. So that the data are substantive categories which are then interpreted with references, references, and scientific references. The theory used in this research is Roland Barthes' semiotics by analyzing it through cinematographic techniques in the field of photography, then interpreting it with denotative, connotative, and mythical meanings. Roland Barthes' semiotics has two significances, the first is the denotation stage, which is the most tangible meaning of the sign, and the second stage is the connotation which will explain the meaning of the message. Based on the analysis that has been done on the Tokopedia ad version of Give The Most Meaningful For Meaningful, it can be concluded that some of the connotative denotative signs found in the ad are interconnected following the storyline and give meaning to the moral valuing time with loved ones is important, and simplicity. If you see in the ad, there are signs about negative, selfish, and emotional traits then a sign of a moral message of mutual help and sincerity, basically the story of this ad the director wants to show things about happiness with simplicity by providing unforgettable moments, and sincerity in responding to a problem. Keywords:​Semotic Analysis, Roland Barthes Semiotics, Tokopedia Advertisement Version Give the Most Meaningful to Meaningful